Formulated Beta-Cyfluthrin Shows Wide Divergence in Toxicity among Bird Species - Laura M. Addy-Orduna; María-Elena Zaccagnini; Sonia B. Canavelli; Pierre Mineau (Journal of Toxicology)
It is generally assumed that the toxicity of pyrethroid insecticides to birds is negligible, though few species have been tested. The oral acute toxicity of formulated beta-cyfluthrin was determined for canaries (Serinus sp.), shiny cowbirds (Molothrus bonariensis), and eared doves (Zenaida auriculata). Single doses were administered to adults by gavage. Approximate lethal doses 50 (LD50) and their confidence intervals were determined by approximate D-optimal design. Canaries were found to be substantially more sensitive to formulated beta-cyfluthrin (LD50=(170±41) mg/kg) than the other two species tested (LD50=(2234±544) mg/kg and LD50=(2271±433) mg/kg, resp.). The LD50 obtained for canaries was also considerably lower than typical toxicity values available in the literature for pyrethroids. This study emphasizes the need for testing a broader range of species with potentially toxic insecticides, using modern up and down test designs with minimal numbers of birds.